Communication for Food and Nutrition Security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
The interviews in this pack feature seven participants at the workshop... They represent different types of organisations, including farmers? organisations, government communication departments, and international bodies such as FAO.